2020
DOI: 10.1186/s40068-020-00188-z
|View full text |Cite
|
Sign up to set email alerts
|

Little Akaki River sediment enrichment with heavy metals, pollution load and potential ecological risks in downstream, Central Ethiopia

Abstract: Addis Ababa City’s river ecosystem is under extreme pressure as a result of inappropriate practices of dumping domestic and industrial wastes; thus, threatening its ability to maintain basic ecological, social and economic functions. Little Akaki River which drains through Addis Ababa City receives inorganic and organic pollutants from various anthropogenic sources. Most of inorganic pollutants such as toxic heavy metals released into the river are eventually adsorbed and settle in the sediment. The objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…For example, higher concentrations have been reported for Fe, Cu, and Mn [16,17], Zn [7,18,19], Cr [7,16,17,20], Pb [16] and As [7,17] in the river and irrigation water in the downstream, in comparison to the upstream of the Akaki catchment. Higher concentrations of Zn, Cu, Mn, Cr, and Pb [8] and Zn and Pb [21] have also been found in river sediments in the downstream of the catchment compared to the upstream. However, a few studies reported higher levels of trace elements in the upstream of the catchment.…”
Section: Introductionmentioning
confidence: 97%
“…For example, higher concentrations have been reported for Fe, Cu, and Mn [16,17], Zn [7,18,19], Cr [7,16,17,20], Pb [16] and As [7,17] in the river and irrigation water in the downstream, in comparison to the upstream of the Akaki catchment. Higher concentrations of Zn, Cu, Mn, Cr, and Pb [8] and Zn and Pb [21] have also been found in river sediments in the downstream of the catchment compared to the upstream. However, a few studies reported higher levels of trace elements in the upstream of the catchment.…”
Section: Introductionmentioning
confidence: 97%